2021
DOI: 10.3389/fendo.2021.744628
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose Tissue Activation by Cold Treatment Ameliorates Polycystic Ovary Syndrome in Rat

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine disease accompanied by energetic metabolic imbalance. Because the etiology of PCOS is complex and remains unclear, there is no effective and specific treatment for PCOS. It is often accompanied by various metabolic disorders such as obesity, insulin resistances, and others. Activated brown adipose tissue (BAT) consumes excess energy via thermogenesis, which has positive effects on energy metabolism. Our previous research and that of others indicates that B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…BAT activity tends to decrease in patients with PCOS owing to high central adiposity and obesity [ 77 ]. A recent report indicated that cold exposure was beneficial for the treatment of PCOS as it reduced the levels of circulating testosterone and luteinizing hormone (LH), the expression of steroidogenic enzymes, inflammatory factors, and cystic ovarian follicles in rats with PCOS [ 78 ]. Additionally, BAT transplantation ameliorated PCOS phenotypes by improving insulin resistance and infertility in mice and rats [ 79 , 80 ].…”
Section: Physiological Role Of Brown Fatsmentioning
confidence: 99%
“…BAT activity tends to decrease in patients with PCOS owing to high central adiposity and obesity [ 77 ]. A recent report indicated that cold exposure was beneficial for the treatment of PCOS as it reduced the levels of circulating testosterone and luteinizing hormone (LH), the expression of steroidogenic enzymes, inflammatory factors, and cystic ovarian follicles in rats with PCOS [ 78 ]. Additionally, BAT transplantation ameliorated PCOS phenotypes by improving insulin resistance and infertility in mice and rats [ 79 , 80 ].…”
Section: Physiological Role Of Brown Fatsmentioning
confidence: 99%
“…Given that the TGF-β–MST1 axis is known to suppress the development of BAT, the inhibition of this axis by follistatin was demonstrated to lead to WAT browning, mitochondrial biogenesis and thereby the activation of BAT thermogenesis [ 193 ]. The activation of BAT in rats with PCOS by cold exposure reduced the circulating levels of testosterone and LH and decreased ovarian expression of steroidogenic enzymes, leading to improved ovulation and fertility [ 194 ]. Thus, follistatin has been suggested to have therapeutic potential for the treatment of metabolic disorders and PCOS through the increase in BAT mass and activity [ 193 ].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…In rat PCOS models, the whitening of BAT can be observed. In this model, BAT whitening could be reversed by the cold exposure of rats with PCOS (4 °C for 20 days), and the batokines secreted by the reactivated BAT normalized the estrous cycle, decreased the serum levels of testosterone, LH and inflammatory factors and led to improved ovulation [ 194 ]. Notably, transplantation of BAT was reported to reverse polycystic ovaries, and improve infertility and IR in rodents with PCOS [ 111 ].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…However, the health benefits of cold exposure were inconsistent in patients and animals ( 85 , 86 ). A recent study showed that cold exposure to 4°C for 20 days reversed the acyclicity of the oestrous cycle and reduced the circulating levels of testosterone and luteinizing hormone (LH) by activating endogenous BAT in rats with PCOS ( 87 ). Furthermore, the expression of steroidogenic enzymes and inflammatory factors was significantly reduced in the ovaries of rats with PCOS.…”
Section: Bat As a Novel Management Strategy For Polycystic Ovary Synd...mentioning
confidence: 99%
“…Furthermore, the expression of steroidogenic enzymes and inflammatory factors was significantly reduced in the ovaries of rats with PCOS. Histological analysis showed that cold exposure significantly improved ovulation and fertility with a reduction in cystic ovarian follicles and an increase in the corpus luteum in rats with PCOS ( 87 ). These findings indicate that cold exposure may be a novel strategy for the treatment of PCOS.…”
Section: Bat As a Novel Management Strategy For Polycystic Ovary Synd...mentioning
confidence: 99%